Observations and interpretation of seasonal ERS-1 wind scatterometer data over northern Sahel (Mali) - Frison, P.L.; Mougin, E.; Hiernaux, Pierre H.Y. (Elsevier, 1998)
This article presents an analysis of ERS-1 wind-scatterometer (WSC) data acquired over a region located in the northern Sahel. The considered period extends from January 1992 to December 1995, that is, covering four vegetation cycles. Experimental observations show that WSC responses at 45° of incidence angle display a marked seasonality associated with the development and senescence of annual grasses during the successive rainy seasons. The interpretation of the ° temporal plots is performed with the assistance of a semiempirical backscattering model combined with an ecosystem grassland model. Contributions of the various components of the Sahelian landscape to the total backscattering are identified. Overall, the soil contribution is always large but the °(45) temporal plots reflect well the vegetation development. The analysis of the different contributions leads to a simplification of the backscattering model. Finally, this latter is parameterized as a function of two surface parameters, namely, the soil volumetric water content and the vegetation biomass. This simplified model allows the vegetation biomass to be estimated with a 33% error.